Principal Leadership Strategies for Improving Teacher Performance - Ika Kania Putri; Bukman Lian; Pahlawan Pahlawan (Yayasan Sembilan Pemuda Indonesia, 2027)
This article describes the principal leadership strategies used to improve teacher performance at SD Negeri 01 Kangkung, Semendawai Barat, Ogan Komering Ulu Timur, South Sumatra. The study was adapted from a descriptive qualitative thesis that focused on four strategic stages: planning, implementation, evaluation, and follow-up. Data were collected through in-depth interviews with the principal and teachers, direct observation of school leadership and teacher performance, and documentation review of school planning, supervision, evaluation, and professional development records. The findings show that leadership planning was conducted through needs analysis, teacher discussion, school meetings, and the preparation of structured programs such as academic supervision, internal training, workshops, and teacher working group activities. The implementation stage reflected a democratic, open, and persuasive leadership style, supported by academic supervision, motivation, appreciation, role modeling, and a harmonious working climate. The evaluation stage was carried out through periodic monitoring, classroom supervision, administrative checks, and feedback, although the depth of feedback and follow-up recommendations still requires strengthening. The follow-up stage included coaching, additional training, support for professional development, digitalization of learning administration, and the use of platforms and artificial intelligence tools to help teachers prepare learning modules. Overall, the leadership strategy created a supportive school climate and contributed to teacher discipline, commitment, instructional preparation, and professional growth. The study recommends strengthening documentation of innovation, expanding teacher participation, intensifying feedback, and increasing the continuity of professional development programs.